The Significance of the Phitsanulok Dhammakaya Inscription for the Dating and Character of Boran (Ancient) Practices in Southeast Asian Theravada Buddhism. (6th September 2022) - Choompolpaisal, Phibul; Skilton, Andrew
Abstract : This article examines the Phitsanulok Dhammakaya inscription of 1549 and other sources for the anonymous post-canonical recitation text called Dhammakaya. It discusses the significance of their paratextual framing and the conclusions that can be drawn from it. An annotated transcription and translation of the text is provided. We argue that the inscription provides the earliest objectively verifiable date for the traditional or non-reform type of Theravada practices elsewhere called boran (ancient) practices. These practices include a specific pre-modern form of boran kammatthan (ancient meditation), Buddha image consecration and/or recitation. The article examines in some detail the context of the patronage and installation of the inscription, and includes a review of the historical evidence for this period, showing unambiguously that this form of Theravada received royal patronage in Siam during the Ayutthaya period in the sixteenth century. This is consistent with recent findings that establish its continued royal patronage in Ayutthaya and then Kandy two centuries later. The article is split into four sections: 1. the boran kammatthan context; 2. the Dhammakaya text; 3. the historical context for the inscription; 4. conclusions regarding its significance.